Early weaning alters redox status in the hippocampus and hypothalamus of rat pups. Issue 6 (29th July 2020) - Rodrigues, Karoline dos Santos; Klein, Caroline Peres; August, Pauline Maciel; dos Santos, Bernardo Gindri; Hözer, Régis Mateus; Maurmann, Rafael Moura; Scortegagna, Mariana Crestani; Hoppe, Juliana Bender; Matté, Cristiane
Abstract: Exposure to environmental factors can program the metabolism, conferring resistance or increasing the risk to chronic disease development in childhood and adulthood. In this sense, lactation is an important period in this window of development. Herein, we investigated the effect of early weaning on neurochemical and behavioral changes in offspring at weaning and adulthood. Female and male pups were divided into four groups: (1) Control weaning (weaning on the PND21, pups were kept with the biological mother); (2) Early Weaning Bromocriptine group (EWB) (pharmacological weaning on PND16); (3) Early Weaning Cross‐Fostering group (EWCF) (pups housed with a foster mother on PND16 up to PND21); (4) Early Weaning Without Care group (EWWC) (weaning on PND16, maternal separation). Weight control of pups was recorded from postnatal Day 16 to 59. On the 21st day, part of the pups was euthanized and the hippocampus and hypothalamus were removed for biochemical evaluation. The remaining pups were submitted to behavioral tests on the 60th postnatal day. Early weaning reduced the pups' body weight, in a sex‐dependent way. At 60 days of age, male pups of EWCF and EWWC groups have lower body weight compared to control male, and female body weight was lower than male pups. In relation to biochemical changes in the brain, weaning altered the levels of oxidants, increased the enzymatic activity of superoxide dismutase (SOD), and glutathione peroxidase (GPx), as well as induced lipid peroxidation. Weaning was also able to alter long‐term memory and induce anxious behavior in pups. Our results demonstrate that the different types of early weaning changed the parameters of redox status in the hippocampus and hypothalamus of pups (21 days old), suggesting a prooxidative profile, in addition, to alter learning/memory and inducing an anxious behavior in male offspring (60 days old). Abstract : Early weaning affected negatively pups' body weight. Early weaning was able to change the redox state in the pups' brains. Pharmacologically early‐weaned male pups presented memory impairment. Female and male offspring were affected differently by early weaning.